Editorial: Was denken Lehrende über Lehre? - Robert Kordts-Freudinger; Daniel Al-Kabbani; Diana Urban; Tobias Zenker; Niclas Schaper (Forum Neue Medien in der Lehre Austria, 2013)
Editorial 2013 | Robert Kordts-Freudinger, Daniel Al-Kabbani, Diana Urban, Tobias Zenker & Niclas Schaper (Paderborn)